Topography of Washington Sound, Wash., San Juan and Henry Islands, (1894) - United States. Coast and Geodetic Survey; Gilbert, J. J. (Washington : The Survey, 1894)
1 map. Relief shown by contours. At head of title: Section XI. "Sheet no. 7." "T-2194." For more sheets from this set of topographic maps of the San Juan Islands as well as more information refer to the index page here. Scale 1:10,000.